Wrongful Convictions Without Punishment Trought Judicial Pardon Perspective Fiqh Islamic Criminal Law - Junaedy, Achmad; Marlina, Andi; Kholid, Muhammad; Waeno, Muhamadaree (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
This research aims to explore the concept of judicial forgiveness in criminal law reform and assess justice in criminal judgments from an Islamic law perspective. The research method used is normative legal research focusing on wrongful conviction without punishment in Islamic law and the new Criminal Code (KUHP). The data was collected through a desk study, in which the researcher analyzed various sources such as books, legal regulations, and academic journals. This research contributes significantly by highlighting the importance of judicial forgiveness in criminal law reform, particularly in achieving holistic justice for victims and perpetrators. By emphasizing human values and Islamic principles, this research presents a comprehensive view of how judicial forgiveness can be an alternative to the compensation system. The research findings emphasize that judicial forgiveness is a crucial step in improving the efficiency of the corrections system, reducing prison overcrowding, and restoring the social balance disrupted by crime. The research proposes that a judicial forgiveness approach can reduce reliance on imprisonment as the sole form of punishment, which is often ineffective and unfair, especially in minor crimes.